Analysis of acid-base properties of some p-substituted aromatic hydrazones in aqueous perchloric acid by spectrophotometric and semiempirical methods - Jankulovska, Mirjana Stojan; Spirevska, Ilinka (Society of Chemists and Technologists of Macedonia, 2014)
The acid-base properties of some p-substituted aromatic hydrazones were examined in aqueous perchloric acid medim by spectrophotometric methods. The possible site where the proton may take place and the stability of the protonated form was discussed using the values of the total energy, binding energy, heat of formation and proton affinity calculated according to the semiempirical methods AM1 and PM3. Furthermore, the stability of the protonated forms, as well as, the stability of the isomers (E and Z) was discussed. Electronic absorption studies were utilized for determination of the dissociation constants of the protonated form (pKBH+), numerically and graphically, at different ionic strength (0.1, 0.25 and 0.5 mol/dm3), as well as, thermodynamic dissociation constants.  The influence of the solvent on the appearance of the recorded spectra was compensated by the use of the method of characteristic vector analysis (CVA).